Insights into the mechanisms, regulation, and therapeutic implications of extracellular matrix stiffness in cancer - Ximo Zhang; Abdullah Al‐Danakh; Xinqing Zhu; Dan Feng; Linlin Yang; Haotian Wu; Yingying Li; Shujing Wang; Qiwei Chen; Deyong Yang (Bioengineering & Translational Medicine)
Abstract The tumor microenvironment (TME) is critical for cancer initiation, growth, metastasis, and therapeutic resistance. The extracellular matrix (ECM) is a significant tumor component that serves various functions, including mechanical support, TME regulation, and signal molecule generation. The quantity and cross‐linking status of ECM components are crucial factors in tumor development, as they determine tissue stiffness and the interaction between stiff TME and cancer cells, resulting in aberrant mechanotransduction, proliferation, migration, invasion, angiogenesis, immune evasion, and treatment resistance. Therefore, broad knowledge of ECM dysregulation in the TME might aid in developing innovative cancer therapies. This review summarized the available information on major ECM components, their functions, factors that increase and decrease matrix stiffness, and related signaling pathways that interplay between cancer cells and the ECM in TME. Moreover, mechanotransduction alters during tumorogenesis, and current drug therapy based on ECM as targets, as well as future efforts in ECM and cancer, are also discussed.